Aggressive dominance can decrease behavioral complexity on subordinates through synchronization of locomotor activities - Alcala, Rocio Soledad (2019)
Alcala, Rocio. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas, Físicas y Naturales; Argentina.